2001
DOI: 10.1063/1.1375136
|View full text |Cite
|
Sign up to set email alerts
|

Thickness and drainage of perfluoropolyethers under compression

Abstract: Compressibility and strength of nanocrystalline tungsten boride under compression to 60GPa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Many of these liquids, including Demnum-S20, exhibit solidlike behavior during shearing ͑a finite yield stress is needed to initiate sliding͒. 11,[13][14][15] In our blow-off experiments with Demnum-S20, neither enhancement of viscosity nor solidification is observed, which is consistent with our previous results 3 using Fomblin-Z. We attribute the viscosity increase and yield stress observed in SFA experiments to confinement of molecules between the two solid surfaces with an applied normal stress.…”
Section: Surface-force-apparatus "Sfa…supporting
confidence: 93%
See 1 more Smart Citation
“…Many of these liquids, including Demnum-S20, exhibit solidlike behavior during shearing ͑a finite yield stress is needed to initiate sliding͒. 11,[13][14][15] In our blow-off experiments with Demnum-S20, neither enhancement of viscosity nor solidification is observed, which is consistent with our previous results 3 using Fomblin-Z. We attribute the viscosity increase and yield stress observed in SFA experiments to confinement of molecules between the two solid surfaces with an applied normal stress.…”
Section: Surface-force-apparatus "Sfa…supporting
confidence: 93%
“…This decrease is presumably caused by both of ends of the Fomblin-Zdol chain being attracted to the substrate, instead of just one end as for Demnum-SA, reducing the degree that the polymer chain extends from the substrate. Xu et al 11 argue that a linear polymer attached at only one end should extend on average & times further away from the substrate than a polymer attached at both ends.…”
Section: Figures 2 and 3 Show Examples Of The Thickness Profilesmentioning
confidence: 99%
“…Therefore, the results shown in Figs the molecule is non-polar and is physically adsorbed onto the solid surface only by van der Waals force [16,17]. Moreover, it was reported that the liquid lubricant was completely squeezed out by the drainage experiment using an SFA [18]. Therefore, the error due to insufficient removal of the liquid is regarded as being small.…”
Section: Resultsmentioning
confidence: 87%
“…The responsible friction mechanism of the FAE film is not analogous to that of the commonly used fluorinated liquid lubricants such as PFPEs (which behave as a typical liquid lubricant) 28,29 but rather close to that of fluorocarbon (FC) monolayers. The FAE film consists of two adsorbed layers on mica substrates which act as fluorinated coatings, and no "mobile" middle layers exist.…”
Section: Discussionmentioning
confidence: 95%